KAJIAN PARAMETER KEBERADAAN VEKTOR PENYAKIT DEMAM BERDARAH DENGUE (DBD) MENGGUNAKAN DUKUNGAN PENGINDERAAN JAUH (REMOTE SENSING) DI KOTA PONTIANAK - Asmadi Asmadi; Akhmad Arif Amin; Sri Budiarti; Machmud Arifin Raimadoya (Graduate School Bogor Agricultural University (SPs IPB), 2011)
Dengue Hemorrhagic Fever (DHF) transmission dynamic is naturally influenced by fluctuating environmental conditions that could be locally specific even at the level of urban areas. Remote sensing technology is increasingly recognized as a powerful tool to scan DHF endemic areas and could be used to monitor DHF vectors fluctuation and the related biogeographical environment. A study was conducted to estimate the DHF transmission intensity in four endemic distric in Pontianak urban areas West Borneo. The estimation was based on environmental condition and the most of the data were obtained through remote sensing using the satellite IKONOS and NOAA. The study subjects were the environmental conditions of the urban areas considered as the risk factors for DHF transmission. Data were collected either through field observations and remote sensing. Data set was analyzed with the discriminant analysis module using the SPSS 17.0. The results of the study showed that there were predictor variables of the environment risk factors should be considered in the estimation of DHF transmission intensity in certain DHF endemic distric. Those variables included: (1) air temperature, (2) mosquito vector density, (3) relative humidity and (4)building density. Linear discriminant function was obtained to predict the incidence of DHF outbreak. Applying this model, DHF transmission intensity in certain distric could be estimated with a high accuracy. The result showed that the assessment model could be built following the formula:Y = 237,490 + 113,474 x (vector) – 121,828 x (temperature) – 98,999 x (relative humidity) + 78,782 x (building) that could be as high accuracy as 90,9 %. Keywords: Remote sensing technology, Dengue Hemorrhagic Fever (DHF), DHF transmission intensity, Mosquito vektor density, IKONOS, NOAA